Dancing With Land: An Asynchronous Artist Panel - Gerecke, Alana; Olson, Michelle; Lebel, Julie; Davies, Olivia C.; Su-Feh, Lee (Performance Matters, 2021)
In this forum, I bring a set of five questions about dancing with land to five contemporary dance practitioners based in and around the city colonially known as Vancouver, constructed on the unceded and ancestral territories of the xʷməθkʷəjˀəm (Musqueam), Sḵwx̱wú7mesh (Squamish), and səl̓ilwətaɁɬ (Tsleil Waututh) First Nations. The artists featured include Michelle Olson of Raven Spirit Dance, Julie Lebel of Foolish Operations, Olivia C. Davies of O.Dela Arts, the OURO Collective, and Lee Su-Feh of battery opera. The questions build on my ongoing research (both academic and artistic) into the politics and kinaesthetics of site- or land-based movement. I seek to spotlight the grounded, refined, and body-based knowledge that dancers and choreographers cultivate in the articulation of their practice.